2021
DOI: 10.5713/ajas.19.0881
|View full text |Cite
|
Sign up to set email alerts
|

Identification of markers associated with estimated breeding value and horn colour in Hungarian Grey cattle

Abstract: Objective: This study was conducted to estimate effect of single nucleotide polymorphisms (SNP) on the estimated breeding value of Hungarian Grey (HG) bulls and to find markers associated with horn colour.Methods: Genotypes 136 HG animals were determined on Geneseek high-density Bovine SNP 150K BeadChip. A multi-locus mixed-model was applied for statistical analyses.Results: Six SNPs were identified to be associated (–log<sub>10</sub>P>10) with green and white horn. These loci are located on chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A new locus never described before in chicken and related to pigmentation is the one mapped on GGA 1 around 100 Mb. Here, 3 genes are located, namely Chondrolectin ( CHODL ) , Transmembrane Serine Protease 15 ( TMPRSS15 ), and Neural Cell Adhesion Molecule 2 ( NCAM2 ) , which are involved in horn pigmentation in cattle ( Zsolnai et al, 2021 ). In detail, NCAM2 is implicated in the chondrogenesis in chicken embryo ( Fang and Hall, 1995 ), hence it could have a low P -value due to its involvement in general shank phenotype (like in cattle horn phenotype, according to Zsolnai et al, 2021 ), but not specifically in pigmentation of the shank.…”
Section: Discussionmentioning
confidence: 99%
“…A new locus never described before in chicken and related to pigmentation is the one mapped on GGA 1 around 100 Mb. Here, 3 genes are located, namely Chondrolectin ( CHODL ) , Transmembrane Serine Protease 15 ( TMPRSS15 ), and Neural Cell Adhesion Molecule 2 ( NCAM2 ) , which are involved in horn pigmentation in cattle ( Zsolnai et al, 2021 ). In detail, NCAM2 is implicated in the chondrogenesis in chicken embryo ( Fang and Hall, 1995 ), hence it could have a low P -value due to its involvement in general shank phenotype (like in cattle horn phenotype, according to Zsolnai et al, 2021 ), but not specifically in pigmentation of the shank.…”
Section: Discussionmentioning
confidence: 99%
“…One of the SNP associated with milk yield from chromosome 9 is ARS-BFGL-NGS-26381, nearest gene being ASF1A (anti-silencing function 1A histone chaperone). Whereas considered candidate gene for meat quality and body composition on chicken, Zsolnai et al (2021) reported association with birth and 205 days weight, with daily gain and maternal traits at Hungarian Grey cattle breed. This SNP seem to be highly connected with maternal abilities of the cows.…”
Section: Genome-wide Association Analysismentioning
confidence: 99%
“…Microsatellite markers are widely used in population genetics, conservation genetics, and parentage identification [ 16 19 ]. In recent years, several genetic analyses have been performed in cattle populations based on microsatellite markers [ 11 , 17 , 20 , 21 ]. Since no previous studies have been made concerning the genetic structure of Angus cattle in Hungary, we aimed to provide breeders with sufficient information to preserve and protect the genetic diversity of the breed and to indicate those herds, which demand special consideration by the HHAGA.…”
Section: Introductionmentioning
confidence: 99%